Podmioty służby zdrowia w PRL - Raduła, Michał (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
In the current legislation, the public tasks related with healthcare are performed by the healthcare entities. In the totalitarian and authoritarian Polish People’s Republic, the healthcare was functioning as a communist health and social welfare system. It was a centralised structure with the main role of the Ministry of Health. The article shows the most important regulations in the field of healthcare system entities in the Polish People’s Republic.
Keywords: służba zdrowia; Polska Rzeczpospolita Ludowa; zespoły opieki zdrowotnej; świadczenia opieki zdrowotnej finansowane ze środków publicznych